2018
DOI: 10.1186/s13014-018-0991-4
|View full text |Cite
|
Sign up to set email alerts
|

Partial breast irradiation with CyberKnife after breast conserving surgery: a pilot study in early breast cancer

Abstract: BackgroundLocal recurrences after breast conserving treatment are mainly close to the original tumor site, and as such shorter fractionation strategies focused on and nearest mammary gland, i.e. accelerated partial breast irradiation (APBI), have been developed. Stereotactic APBI has been attempted, although there is little experience using CyberKnife (CK) for early breast cancer.MethodsThis pilot study was designed to assess the feasibility of CK-APBI on 20 evaluable patients of 29 eligible, followed for 2 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 48 publications
(50 reference statements)
1
27
1
1
Order By: Relevance
“…This could be explained by the substantial PTV margin expansion mandated by respiratory and setup uncertainties in 3D-CRT. Likewise, our delicate S-PBI planning achieved consistent dosimetric profiles compared to those observed in Western S-PBI studies in other organs-atrisk, without compromising PTV coverage or creating PTV hot spots (9,21,22). These results demonstrated that S-PBI could overcome the disadvantage of relatively small breast volumes in Korean women.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…This could be explained by the substantial PTV margin expansion mandated by respiratory and setup uncertainties in 3D-CRT. Likewise, our delicate S-PBI planning achieved consistent dosimetric profiles compared to those observed in Western S-PBI studies in other organs-atrisk, without compromising PTV coverage or creating PTV hot spots (9,21,22). These results demonstrated that S-PBI could overcome the disadvantage of relatively small breast volumes in Korean women.…”
Section: Discussionsupporting
confidence: 62%
“…As a result, not only were the ipsilateral breast dosimetric goals successfully satisfied in all breasts in our study, but the median ipsilateral breast V 50% in our study was 35.8%, much lower than that of the KROG study (20). Compared to the Western A-PBI reports (Table S2), the ipsilateral breast V 50% in our patients was as low as those in Western S-PBI studies (9,21,22), and dramatically lower than in A-PBI studies using three-dimensional conformal radiation therapy (3D-CRT), ranging from 42 to 49% (23)(24)(25)(26). This could be explained by the substantial PTV margin expansion mandated by respiratory and setup uncertainties in 3D-CRT.…”
Section: Discussioncontrasting
confidence: 42%
“…Very mild toxicities occurred, 100% of the patients had good-excellent cosmesis. Lozza et al published a pilot study in 2018, they treated 20 patients with CK-SAPBI using the Iris collimator [ 32 ]. The total dose was 30 Gy in 5 consecutive fractions and were prescribed to the isodose line include 95% of the PTV.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the reduced number of fractions, there is a possibly larger impact of a geographical miss of the target, with hence a potential increase in the risk of local recurrence. Most current hypofractionated external beam APBI (EB-APBI) protocols use daily online positioning verification and correction based on cone beam CT or kV imaging, or more recently MR imaging [13,[15][16][17]. The motion that occurs after this setup and during the treatment delivery, is often not considered.…”
Section: Introductionmentioning
confidence: 99%